The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.55606/jurdikbud.v1i3.87
|View full text |Cite
|
Sign up to set email alerts
|

Quizizz Atau Kahoot, Gamifikasi Dalam Pembelajaran Bahasa Inggris

Abstract: Gamification is the comprehensive use of game features with the aim of improving student’s performance and motivation in learning. The purpose of this present research is to conduct a systematic review of previous relevant research using the Quizizz and Kahoot! in learning English during 2021. The research method employed a Literature Study through a search on the Google Scholar page. Synthesis of literature data was analyzed from various components of students’ needs in learning English using Quizziz and Kaho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…This approach also aims to make VAE more practical, creative, and result-oriented. Past studies have shown, the gamification approach has received positive acceptance in various educational fields such as Arabic Language Lutfiyatun (2021), Islamic Education Hambali & Lubis (2022), Chemistry Lutfi et al (2021), Physics Badratusyahryah et al (2022), English Language Sari & Nurani (2021), and Malay Language (Hushaini et al, 2022). However, its use in VAE is still limited and has yet to receive the deserved attention within the education community.…”
Section: Research Backgroundmentioning
confidence: 99%
“…This approach also aims to make VAE more practical, creative, and result-oriented. Past studies have shown, the gamification approach has received positive acceptance in various educational fields such as Arabic Language Lutfiyatun (2021), Islamic Education Hambali & Lubis (2022), Chemistry Lutfi et al (2021), Physics Badratusyahryah et al (2022), English Language Sari & Nurani (2021), and Malay Language (Hushaini et al, 2022). However, its use in VAE is still limited and has yet to receive the deserved attention within the education community.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Kedua aplikasi tersebut memiliki kelebihan yaitu mampu meningkatkan motivasi dan peformansi siswa. (Sari & Nurani, 2021) Quizizz merupakan aplikasi pendidikan berbasis game yang dilengkapi dengan berbagai fitur menarik seperti tema, avatar, musik, dll. Pendidik dapat memasukkan berberapa soal yang akan digunakan baik untuk quiz, pretest, posttest maupun untuk ujian lainnya.…”
Section: Pendahuluanunclassified
“…Gamification is the application of game design to a learning context (Firdaus & Faisal, 2021;Marisa et al, 2022;Mukarromah & Agustina, 2021). The application of gamification has gained many benefits, including (1) more than 90% of participants are interested in participating in mathematics learning using the gamification model (Kristanto, 2020;Ristiana & Dahlan, 2021), (2) there is a positive impact on students in learning the Arabic language (Jasni et al, 2019;Mulia et al, 2023), (3) effectively increasing digital literacy and student engagement in English learning (Pambudi et al, 2019;Sari & Nurani, 2021), ( 4) increase concentration and focus on children in civic education (Januar, 2023;Pradnyana et al, 2020), and (5) there is a positive influence on student activities in science learning in elementary schools (Sudana et al, 2021;Twiningsih Negeri Laweyan No & Surakarta, 2023). However, its application in physics learning is still rare.…”
Section: Introductionmentioning
confidence: 99%